PENULARAN PENYAKIT BUDOK SECARA MEKANIK DAN PENYAMBUNGAN PADA TANAMAN NILAM (Pogostemon cablin Benth) - Alfizar Alfizar (Jurnal Agrista, 2003)
Transmiss.ion of budok disease by mechanic and grafting methods on patchouli (Pogoslemon cablin Benth). Budok is the most serious disease on patchouli in Nanggroe Acch Darussalam Province and considered as a major constraint for patchouli production. The disease is supposed caused by a virus or Micoplasma like organism (MLO). Transmission of budok disease may occur naturally in field. but the mechanism of transmission has not yet been known. The research aimed at investigate wether the budok disease could be transmitted by mechanic sap and grafting method. The results showed that budok disease was transmitted by both method tested. Inoculation time of mechanical transmission by mechanic sap inoculation was faster than grafting method.